Sexy bodies: the strange carnalities of feminism - Grosz, E. A.; Probyn, Elspeth (Routledge, 1995)
Are bodies sexy? How? In what sorts of ways? Sexy Bodies investigates the production of sexual bodies and sexual practices, of sexualities which are dyke, bi, transracial, and even hetero. It celebrates lesbian and queer sexualities but also explores what runs underneath and within all sexualities, discovering what is fundamentally weird and strange about all bodies, all carnalities. Looking at a pleasurable variety of cultural forms and texts, the contributors consider the particular charms of girls and horses, from National Velvet to Marnie; discuss figures of the lesbian body from vampires to tribades to tomboys; uncover 'virtual' lesbians in the fiction of Jeanette Winterson; track desire in the music of legendary Blues singers; and investigate the ever-scrutinised and celebrated body of Elizabeth Taylor. The collection includes two important pieces of fiction by Mary Fallon and Nicole Brossard. Sexy Bodies makes new connections between and amongst bodies, cruising the borders of the obscene, the pleasurable, the desirable and the hitherto unspoken rethinking sexuality anew as deeply and strangely sexy.
Keywords: LGBTQIA2+; approches et analyses; corps; cours; féminisme pop; identités LGBTQIA2+; lesbianisme; lit4700; premier cycle; queer; ressource en ligne; sexualité; thématiques